Processing stage flexibility of the SNARC effect: Task relevance or magnitude relevance? - Xiang, Xinrui; Yan, Lizhu; Fu, Shimin; Nan, Weizhi (Frontiers in Psychology, 2022)
Previous studies have shown that the processing stage of the spatial-numerical association of response codes (SNARC) effect was flexible. Two recent studies by Nan et al. (2022) and Yan et al. (2021) used the same experimental paradigm to check whether the SNARC effect occurred in the semantic-representation stage but reached contradictory conclusions, showing that the SNARC effect was influenced by a magnitude Stroop effect in a magnitude comparison task but not by a parity Stroop effect in a parity judgment task. Those two studies had two distinct operational factors: the task type (magnitude comparison task or parity judgment task, with the numerical magnitude information task-relevant or task-irrelevant) and the semantic representation stage-related interference information (magnitude or parity Stroop effect, with the interference information magnitude-relevant or magnitude-irrelevant). To determine which factor influenced the SNARC effect, in the present study, the Stroop effect was switched in the two tasks based on the previous studies. The findings of four experiments consistently showed that the SNARC effect was not influenced by the parity Stroop effect in the magnitude comparison task but was influenced by the magnitude Stroop effect in the parity judgment task. Combined with the results of Nan et al. (2022) and Yan et al. (2021), the findings indicated that regardless of the task type or the task-relevance of numerical magnitude information, magnitude-relevant interference information was the primary factor to affect the SNARC effect. Furthermore, a two-stage processing model that explained the observed flexibility of the SNARC effect was proposed and discussed.